Usulan Perbaikan Rantai Pasok dengan Penerapan Metode Supply Chain Operation Reference (SCOR) - 10070219036, RB. Bagus Bimantoro; Rakhmat Ceha; M Dzikron AM (Bandung Conference Series: Industrial Engineering Science, 2024)
Abstract. The market is filled with diverse customer needs and desires which can influence demand uncertainty. PT. Kramat Hidro Mandiri is the manufacturing company that implements a Make To Order (MTO) strategy. This company produces Sprinklers which function as watering tools for agricultural irrigation systems. Customer taking repeat order from Make To Order (MTO) based companies have the potential to lack thorough preparation if there is uncertainty in demand. The research objectives include identifying the current condition of supply chain flow, evaluating supply chain performance, analyzing the causes and consequences of not reached targets supply chain performance, and planning for improvement the supply chain system. The research variables studied are a set of Supply Chain Operation Reference (SCOR) method metrics and are codified in the form of list KPI (Key Performance Indicator). Data collection consists of Product Specifications, KPI Identification Data, KPI Validation Data, KPI Actual Measurement Data, and SCOR Metric Importance Data. The results of the research include identifying the current supply chain flow conditions where there are still inefficiencies because the testing process was carried out twice and the handling of product defects has not been procedurally effective. Supply chain performance measurements are carried out to obtain KPIs that do not reach targets performance. Meanwhile, determining the priority of improving the SCOR Metric is an urgency to improve the current condition of supply chain flows. Proposed improvements to the supply chain system through the Digital Supply Chain concept with integration of ERP System and RFID System. Abstrak. Pasar dipenuhi dengan beragam kebutuhan dan keinginan pelanggan yang dapat mempengaruhi ketidakpastian permintaan. PT. Kramat Hidro Mandiri ialah perusahaan manufaktur yang menerapkan strategi Make To Order (MTO). Perusahaan ini memproduksi Sprinkler yang berfungsi sebagai alat penyiraman untuk sistem irigasi pertanian. Pelanggan melakukan pemesanan repeat order terhadap perusahaan berbasis Make To Order (MTO) berpotensi kurangnya persiapan yang matang apabila terdapat ketidakpastian permintaan. Tujuan penelitian antara lain mengidentifikasi kondisi aliran rantai pasok saat ini, mengevaluasi kinerja rantai pasok, menganalisis sebab-akibat ketidaktercapaian target kinerja rantai pasok, dan merencanakan usulan perbaikan sistem rantai pasok. Variabel penelitian yang diteliti berupa sekumpulan metrik metode Supply Chain Operation Reference (SCOR) dan dikodifikasi dalam bentuk KPI (Key Performance Indicator). Pengumpulan Data terdiri dari Spesifikasi Produk, Data Identifikasi KPI, Data Validasi KPI, Data Pencapaian Aktual KPI, dan Data Tingkat Kepentingan Metrik SCOR. Hasil penelitian antara lain identifikasi kondisi aliran rantai pasok saat ini masih terdapat ketidakefisiensian karena proses pengujian dilakukan 2 kali dan penanganan kecacatan produk belum efektif secara prosedur. Pengukuran kinerja rantai pasok dilakukan untuk memperoleh KPI yang tidak memenuhi target kinerja. Adapun, penentuan prioritas perbaikan Metrik SCOR sebagai urgensi memperbaiki kondisi aliran rantai pasok saat ini. Usulan perbaikan sistem rantai pasok melalui konsep Digital Supply Chain dengan integrasi Sistem ERP dan Sistem RFID.